2017
DOI: 10.31436/imjm.v16i2.1048
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Of MYO1H Single Nucleotide Polymorphism In Class III Malocclusion With Mandibular Prognathism: A Preliminary Study

Abstract: Introduction: Evidence suggests that several genes; including MYO1H, play an important role in the etiology of Class III malocclusion. Single nucleotide polymorphism (SNP) in marker rs10850110 (locus 12q24.11) within MYO1H gene has been associated with the incidence of mandibular prognathism (MP). MYO is a class 1 myosin that is responsible for the synthesis of Matrilin-1; an important protein involved in the formation of cartilage's extracellular matrix, hence is implicated in the formation of mandibular cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Cruz et al 31 used the TaqMan method of real-time PCR to amplify the genome and demonstrated that the polymorphism of rs10850110 in MYO1H, GHR, and FGF genes plays a role in mandibular prognathism and maxillomandibular discrepancies. Yahya et al 32 on the Malay population also showed the role of SNP (rs10850110) MYO1H in class-III mandibular prognathism patients as a risk factor. Da Fontoura et al on Romanian and American populations showed that the G allele of rs10850110 polymorphism of the MYO1H gene being overrepresented in skeletal class-III patients.…”
Section: Discussionmentioning
confidence: 94%
“…Cruz et al 31 used the TaqMan method of real-time PCR to amplify the genome and demonstrated that the polymorphism of rs10850110 in MYO1H, GHR, and FGF genes plays a role in mandibular prognathism and maxillomandibular discrepancies. Yahya et al 32 on the Malay population also showed the role of SNP (rs10850110) MYO1H in class-III mandibular prognathism patients as a risk factor. Da Fontoura et al on Romanian and American populations showed that the G allele of rs10850110 polymorphism of the MYO1H gene being overrepresented in skeletal class-III patients.…”
Section: Discussionmentioning
confidence: 94%
“…MYO1H was previously identified to be associated with mandibular prognathism or mandibular retrognathism ( Yahya et al, 2007 , Arun et al, 2016 ). Previous researches mainly focused on Class III malocclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches mainly focused on Class III malocclusion. Yahya et al , reported the association of MYO1H rs10850110 and mandibular prognathism in the Malaysian population ( Yahya et al, 2007 ). Conversely, Dalaie et al, reported in the Iranian population a non-significant correlation between MYO1H rs10850110 and skeletal class III due to mandibular prognathism ( Dalaie et al, 2020 ) and the same finding was reported in the Brazilian population by Cunha ( Cunha et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation